The Wiley Blackwell Encyclopedia of Health, Illness, Behavior, and Society 2014
DOI: 10.1002/9781118410868.wbehibs489
|View full text |Cite
|
Sign up to set email alerts
|

Adolescence and Stress

Abstract: The stress that adolescents experience is different from that experienced by adults because they spend their lives in different social spheres than adolescents do. Research on adolescent stress and risk tends to follow an ecological model, which emphasizes the importance of social contexts for shaping youths’ well‐being. Three commonly discussed contexts are family, peers, and school. Stress manifests within each of these domains, but the domains are also interconnected. Stress may spill over from one context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The 30th World Mental Health Day in 2021 in China aimed to call on the entire society to pay attention to and support the mental health promotion of children and adolescents (National Health Commission of the People’s Republic of China - Disease Prevention and Control Center, 2021). Research on adolescents identifies three primary contexts of stressors that might impact their mental health: family, peer networks, and school environment (Rohrman, 2014). Empirical research has also found that perceived stress can affect adolescents’ health issues, relating to more unhealthy eating behaviors (Hill et al, 2018) and mental disorders (Lindholdt et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The 30th World Mental Health Day in 2021 in China aimed to call on the entire society to pay attention to and support the mental health promotion of children and adolescents (National Health Commission of the People’s Republic of China - Disease Prevention and Control Center, 2021). Research on adolescents identifies three primary contexts of stressors that might impact their mental health: family, peer networks, and school environment (Rohrman, 2014). Empirical research has also found that perceived stress can affect adolescents’ health issues, relating to more unhealthy eating behaviors (Hill et al, 2018) and mental disorders (Lindholdt et al, 2022).…”
Section: Introductionmentioning
confidence: 99%